ANALYSIS AND DETERMINATION OF TOURISM CLIMATE INDEX (TCI) IN EAST NUSA TENGGARA - Nizar Manarul Hidayat (Pusat Penelitian dan Pengembangan BMKG, 2022)
The development of tourism is quite rapid in several parts of Indonesia. No exception in East Nusa Tenggara which offers a beautiful part of the beach. Most tourists will use this information in the form of the climate comfort index to determine the right travel time. The Climate Comfort Index can be searched using the Tourism Climate Index (TCI) method including weather parameters such as maximum air temperature and minimum air humidity (Daytime Comfort Index), average air temperature and average air humidity (Daily Comfort Index), rainfall, length of sunshine and average wind speed). Monthly data for the years 1991 - 2015 were provided from eight BMKG meteorological stations. The results showed that the Rote and Maumere regions were in the 'Very Good' category in the summer (June and July). Meanwhile, Sabu and Rote had the most comfortable seven months. In general, during the summer (June - August) the TCI value (≥ 70) has increased so as to provide comfort for beach tourism destinations. The best time for traveling is best visited during the peak of the dry season (June to August) while in the rainy season (November - February) is the worst time to travel.